Patients Empowerment Based on Experimential Learning to Behavior of Acute Compilation Prevention and Blood Glucose Levels of Patients DM - Nunung Ernawati; Suharto Suharto; Yulis Setiya Dewi (Universitas Airlangga, 2015)
Introduction: Acute complications are common in patients with Diabetes Mellitus (DM). To improve the behavior prevention of complications and control blood sugar levels, patients need to be equipped with knowledge about the disease process to built a positive attitude and good behavior. The aim of this study was to analyze the effect of patient empowerment based on experiential learning behavior on the prevention of complications and blood sugar levels.Methods: This study used a quasi-experimental design with pre-post test approach using control groups. Samples were 46 diabetic patients who take control in poly RS Mardi Waluyo Blitar taken by consecutive sampling. Data were collected using a questionnaire and checklist recall. Data were analyzed using paired t test, wilcoxon signed rank test and mann whitney.Results: The patient empowerment-based experiential learning have a significant impact on the behavior of prevention of complications.Discussion: Methods of experiential learning can be applied to improve the self-care of patients, especially those who have experienced an acute complications, so the patient is easier to implement behavioral prevention of complications and control blood sugar levels.